Pollution reduction and operating cost analysis of municipal wastewater treatment in China and implication for future wastewater management. (20th April 2020) - Qi, Miao; Yang, Yongkui; Zhang, Xiaoyan; Zhang, Xiaoqian; Wang, Mengzhu; Zhang, Wei; Lu, Xuebin; Tong, Yindong
Abstract: "Clean water and sanitation" is one of the 17 sustainable development goals recommended by the United Nations. To improve water quality, China had experienced a dramatic improvement in municipal wastewater treatment during 2006–2016; yet the effects on pollutant reductions have not been fully discussed. This study analyzed pollutant reductions and operating costs of municipal wastewater treatment according to an investigation including 1822 active wastewater treatment plants in operation in China. The results showed that, in 2016, a total of 505 Gg of total nitrogen, 140 Gg of ammonia, 29 Gg of total phosphorus, 1296 Gg of chemical oxygen demand and 357 Gg of five-day biochemical oxygen demand were discharged after treatment. The highest pollutant removal efficiency from municipal wastewater was observed in five-day biochemical oxygen demand, with an efficiency of 91.2 ± 6.7% (average and standard deviation), while the lowest removal efficiency was observed in total nitrogen, only with an efficiency of 65.5 ± 13.9%. The higher total phosphorus removal efficiency (80.8 ± 11.8%) by wastewater treatment could increase the ratio of total nitrogen to total phosphorus by about twice in the effluent. Water managers should focus on the potential impacts of effluents to nutrient dynamics and ecology in receiving waters. Modern perspectives on nutrient limitation in aquatic ecosystems will require more N removal from municipal wastewater to achieve the desired water quality outcomes, such as by refining operation of existing facilities, developing efficient N-removal technology and introducing standards for nutrient ratio target in the effluent discharge. Graphical abstract: Image 1 Highlights: We investigated the pollutant conditions in influent and effluent in 1822 WWTPs in operation in China. The lowest pollutant removal efficiency was observed in total nitrogen, with an efficiency of 65.5 ± 13.9%. Higher total phosphorus removal efficiency in the influent largely increased nitrogen: phosphorus ratio in the effluent. A region-based effluent discharge standard based on pollutant control target in watershed should be encouraged.